Comparison of Improvement in Basketball Perimeter Shooting Skills Training Results in Introverted and Extroverted Students of MTsN Bangkalan - Ika Dita Agustina; Fajar Hidayatullah; Haryo Mukti Widodo (Performa, 2026)
This study aims to analyze the comparison of improving basketball perimeter shooting skills between introverted and extroverted students at MTs Negeri Bangkalan. The research method used a pseudo-experimental approach with a pretest-posttest group design involving 24 grade VII students who were divided into two groups based on personality type, each consisting of 12 students. Sampling was done using purposive sampling techniques with the Extrovert and Introverted Personality Inventory questionnaire instrument and a perimeter shooting test. The Micro Cycle training program was carried out for five days of training with a duration of 120 minutes per session, including physical tests, shooting form (BEEF), perimeter shoot, goal setting shoot, and mini games. Data analysis uses the Wilcoxon Signed Rank Test because the data is not normally distributed. The results showed that there was no significant difference between pretest and posttest scores in the introverted (p=0.705) and extroverted (p=0.096) groups. However, the extroverted group showed a tendency to improve better than the introverted group. The provision of UVL-BOCE verbal feedback has not shown a significant effect on the improvement of perimeter shooting skills in both personality types, indicating the need to modify learning methods that are more appropriate to the characteristics of each group.